Faktor Penyebab Timbulnya Masalah Pada Pasangan Pernikahan Usia Muda Di Kenagarian Ampang Pulai Kecamatan Koto Xi Tarusan Kabupaten Pesisir Selatan - Adison, Joni; Suryadi, Suryadi (Holistic Science, 2022)
This kind of research is qualitative descriptive. This research done with interview method with two key subjects marriage young couple and 6 second subjects di Kenagarian Ampang Pulai Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan. This data has been analyzes with tringulation data, after that it data has been analyze with three steps: (1) Reduction data (2) Serving data (3) Conclusion. This research showed that: (1) Physiologist factors caused problem in marriage young couple are the young couple did not act like usual and unless accepted with unwilling child. (2) Psychologits factors caused problem in marriage young couple are unless controlled emotion jealous with couple and unless attention when couple in sick condition and also unless tolerant with poor economic condition, no trusted each other and always negative thinking and also psychic damaged.